Exploring the potential impact of empiric antibiotic de-escalation for suspected early onset neonatal sepsis - Nazedah Ain Ibrahim; Mohd Makmor Bakry; Shareena Ishak; Nurul Ain Mohd Tahir; Noraida Mohamed Shah (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to explore the impact of empiric antibiotic de-escalation for suspected early onset neonatal sepsis (EONS) on clinical and economic outcomes. This was a multicenter prospective cohort study. Newborns were recruited from 3 neonatal intensive care units (NICUs) in Klang Valley, Malaysia.